2019
DOI: 10.1159/000503967
|View full text |Cite
|
Sign up to set email alerts
|

Basic Research and Clinical Reports Associated with Low Serum IgG4 Concentrations

Abstract: Elevated IgG4 concentrations in serum have received a great deal of attention recently, whereas the significance of decreased IgG4 levels was frequently neglected in spite of its close relation with infectious and noninfectious inflammations. In this review, based on the structural and functional characteristics of IgG4, we bring together case reports and research related to low levels of IgG4 and try to scratch the importance of decreased IgG4 concentrations in serum. As with elevated IgG4 levels, low serum I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…In our paper, we found that correct immunization was achieved by children with higher levels of IgG4. Our findings could explain Tian et al findings that link recurrent respiratory infections -particularly pulmonaryand bronchiectasis with IgG4 serum deficiency 27 .…”
Section: Discussionsupporting
confidence: 77%
“…In our paper, we found that correct immunization was achieved by children with higher levels of IgG4. Our findings could explain Tian et al findings that link recurrent respiratory infections -particularly pulmonaryand bronchiectasis with IgG4 serum deficiency 27 .…”
Section: Discussionsupporting
confidence: 77%
“…This raises the possibility that the impact of IgG4 deficiency on mortality may be indirect. Consistent with this notion, recent studies have shown that low serum IgG4 increases the risk of not only respiratory infections but also non-respiratory conditions including allergic, autoimmune, and cardiovascular diseases [ 20 26 ]. For these latter conditions, serum IgG levels appear to be inversely related to the severity of disease [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 82%
“…Although patients with anti-LGI-1 and CASPR2 antibodies are characterized by clinical heterogeneity, they also demonstrate considerable overlap in clinical symptomatology; anti-LGI1 antibodies are most commonly associated with epilepsy and limbic encephalitis, while anti-CASPR2 antibodies are associated with neuromyotonia, Morvan syndrome, and neuropathic pain. Anti-IgLON5 antibodies define a complex syndrome of chronic progressive brainstem symptomatology, gait instability, distinct non-rapid eye movement (REM) and REM parasomnias, sleep-disordered breathing, obstructive sleep apnea, cognitive decline, and movement disorders as recently identified, most commonly craniofacial dyskinesias, chorea, dystonia, and abnormal eye movements [ 3 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Molecular Commonalities Between Musk-mg and Other Autoimmune...mentioning
confidence: 99%